2006
DOI: 10.1186/1471-2407-6-48
|View full text |Cite
|
Sign up to set email alerts
|

CDH1promoter hypermethylation and E-cadherin protein expression in infiltrating breast cancer

Abstract: BackgroundThe E-cadherin gene (CDH1) maps, at chromosome 16q22.1, a region often associated with loss of heterozygosity (LOH) in human breast cancer. LOH at this site is thought to lead to loss of function of this tumor suppressor gene and was correlated with decreased disease-free survival, poor prognosis, and metastasis. Differential CpG island methylation in the promoter region of the CDH1 gene might be an alternative way for the loss of expression and function of E-cadherin, leading to loss of tissue integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
106
1
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 37 publications
9
106
1
3
Order By: Relevance
“…In these cases, methylation specific PCR fragment might be the result of contamination with infiltrating leukocytes, making the detection and interpretation of tumor-associated distorted methylation patterns more complicated (Lombaerts et al, 2004). Overall, our data corroborate the findings reported by earlier studies that CDH1 promoter hypermethylation is responsible for its heterogeneous downregulation in ductal cell carcinoma (Graff et al, 2000;Caldeira et al, 2006;Prasad et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In these cases, methylation specific PCR fragment might be the result of contamination with infiltrating leukocytes, making the detection and interpretation of tumor-associated distorted methylation patterns more complicated (Lombaerts et al, 2004). Overall, our data corroborate the findings reported by earlier studies that CDH1 promoter hypermethylation is responsible for its heterogeneous downregulation in ductal cell carcinoma (Graff et al, 2000;Caldeira et al, 2006;Prasad et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…The frequency of CDH1 methylation in our study is similar to other studies conducted on breast cancer patients (Shinozaki et al, 2005;Prasad et al, 2008). Other previous studies have shown varying frequencies of CDH1 methylation viz; 72% (Caldeira et al, 2006), 26.1% (Hu et al, 2002) , 21.7% (Sebova et al, 2011), 94% (Shargh et al, 2011) in breast cancer tissues from different population. The comparison of normal and malignant tissues showed a statistically significant (p<0.0001) difference in the methylation pattern, thus there was significanteightfold increase in the risk to breast cancer in the subjects with methylated CDH1 promoter.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…CDH1 at 16q22 has been reported as the major candidate gene and is often methylated [40] but do not fulfill our selection criteria. However, PRMT7 coding for an arginine methyltransferase, with unknown relation to cancer prognosis, is additionally upregulated (supplementary Fig.…”
Section: Candidate Genesmentioning
confidence: 99%